Sjögren’s syndrome: history and challenges in diagnosis - Brzdęk, Kinga; Wiśniewski, Szymon; Domańska, Olga; Baran, Wiktor; Brzdęk, Michał (Nursing Problems / Problemy Pielęgniarstwa, 2024)
The aim of this study is to provide a comprehensive review and analysis of current diagnostic methods for Sjögren’s syndrome and to highlight the historical progress in diagnosing dry eye syndrome. The article is based on scientific publications, with relevant articles selected after an initial assessment and analysed using a non-systematic review method to ensure a concise synthesis of available information. Sjögren’s syndrome is a chronic autoimmune disease characterised by lymphocytic infiltration in exocrine glands. Sjögren’s syndrome remains a poorly understood disease, concealing many aspects. This disease often manifests through dryness of the mouth and eyes, as well as skin changes. Over the years, the diagnostic criteria for Sjögren’s syndrome have under-gone multiple modifications. In 2016, a consensus was reached that currently serves as the diagnostic foundation. The diagnostic process is challenging, leading to delayed diagnosis. Therefore, specialists employ supplementary tests, including the Schirmer test, scintigraphy, and histopathological examinations.